Human Resources Strategies Recruitment and its Impact on Achieving Competitive Advantage: An Empirical Study on Qatar Pharma - Al Sulaiti, Mohammed Ibrahim (The Arab Journal of Administration, 2024)
This study aimed at identifying the impact of human resources recruitment strategies on achieving the competitive advantage in Qatar Pharma. In order to achieve the study objectives, the researcher prepared a questionnaire to collect preliminary information from the study sample which consisted of (63) paragraphs. Considering this, data were collected and analyzed and hypotheses were tested using the SPSS program. The study community consisted of all managers and departments’ heads of Qatar Pharma Company and they were (300) employees. Due to the small size of the study community, the researcher followed the complete census method and it was applied to all the members of the study community through the distribution of an electronic questionnaire and of them, (257) individuals responded. After conducting the descriptive analysis of the study and the regression analysis of the hypotheses of the study, the study reached many results, the most important of which was that there was a statistically significant impact at a level less than (0.05) of human resources recruitment strategies on achieving competitive advantage in Qatar Pharma. .